Adsorptional and pharmacopoeial characteristics of new types of activated carbon obtained by thermochemical synthesis from various types of plant raw materials - Lishai, Nastassia V.; Mengwei, Li; Melekhovets, Natallia A.; Tsyhankova, Nadzeia G.; Savitskaya, Tatsiana A.; Hrynshpan, Dzmitry D. (Journal of the Belarusian State University. Chemistry, 2024)
The studies were carried out on both physico-chemical (adsorption capacity; pH) and pharmaceutical (acidity alkalinity; solubility in acid; sulfide content; weight loss on drying; content of ash, fluorescent substances and substances soluble in 96 % alcohol; presence of cations (copper, lead, zinc) and anions (cyanides, chlorides, sulfates)) properties of new types of active carbons obtained by thermochemical synthesis of cellulose- and lignin-containing raw materials. An assessment of their compliance with the requirements of the state pharmacopoeias of the Republic of Belarus and other countries is given.